Od paruzji do „paruzjologii", czyli eschatologia w ujęciu Antoniego Nitroli - Kulik, Bogdan (Poznańskie Studia Teologiczne, 2014)
Death has always brought forth the question about life after death. As the interesting history of eschatology shows, it is not easy to find one simple answer. Therefore, it is hardly surprising that also nowadays new attempts are made to present an image of man’s eternal life. One of them is a proposal by Antonio Nitrola, professor of the Pontifical Gregorian University in Rome, who made the Second Coming of Christ (Parousia) the keyword of his eschatology. According to him, if one can understand that the Second Coming of Christ (Parousia) is an event which brings life, fulfillment and judgment at the same time, then it is possible to find the fullest answer to the question what happens with a man after death. Moreover, eschatology can be called “parousiology”. This article is an attempt to synthetically present the thoughts of this Roman theologian, contained in a two-volume work entitled: Trattato di escatologia. I. Spunti per un pensare escatologico, Cinisello Balsamo (Milano) 2001; II. Pensare la venuta del Signore, Cinisello Balsamo (Milano) 2010.